Visual attention affects temporal estimation in anticipatory motor actions - Marinovic, Welber; Wallis, G. (Springer-Verlag, 2011)
The production of accurate motor actions requires successful extraction of relevant information about the target of that action. By the same token, it also requires the successful exclusion of potentially distracting, irrelevant information. This study sought to determine the impact of transient visual distractions on performance in an anticipatory timing task, in particular the temporal and spatial relationship between distractor and target at which maximal distraction occurs. The results support the notion of a critical temporal and spatial window of distraction which provides insight into the visuomotor processes underlying distraction.